2012
DOI: 10.4236/ajps.2012.32029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen on Yield and Oil Quality of Sunflower (<i>Helianthus Annuus</i> L.) Hybrids under Sub Humid Conditions of Pakistan

Abstract: Sunflower (Helianthus annuus L.) has emerged as an economically important crop in Pakistan due to its significant share in vegetable oil production. The plant metabolic processes require protein to increase the vegetative, reproductive growth and yield of the crop. The protein is wholly dependent upon the amount of nitrogen fertilization available for plant use. ) and grain yield (3809 kg·ha -1 ) compared to the other N rates. The maximum oil content (46.2%) was observed in Hysun-38 without application of N fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 7 publications
4
29
1
2
Order By: Relevance
“…Results were similar in 2011. These results are consistent with those of Abdel-Sabour and Abo El-Seoud (1996), Nanjundappa et al (2001), Munir et al (2007), and Nasim et al (2012), who observed decreases in achene oil percentages with increased N application. Any two means not sharing a letter are significantly different at 5% level of probability (least significant difference LSD); NS: non significant.…”
Section: Achene Oil Contents (%)supporting
confidence: 92%
“…Results were similar in 2011. These results are consistent with those of Abdel-Sabour and Abo El-Seoud (1996), Nanjundappa et al (2001), Munir et al (2007), and Nasim et al (2012), who observed decreases in achene oil percentages with increased N application. Any two means not sharing a letter are significantly different at 5% level of probability (least significant difference LSD); NS: non significant.…”
Section: Achene Oil Contents (%)supporting
confidence: 92%
“…Singh and Quadri (1984) and Sharma and Gaur (1988) have also reported that decreases in oil content (%) in response to high levels of N was due to the presence of more impurities. Protein synthesis is wholly dependent on the amount of N fertilizer available for plant use (Nasim et al, 2012).The application of N fertilizer also increases protein concentration regardless of the irrigation regime used (Jalilian et al, 2012).…”
Section: Correlation Among Crude Fat Content Protein and Fatty Acidmentioning
confidence: 99%
“…Application of organic fertilizer significantly (P 0.05) increased oil and protein contents in both early and late sown sunflower, except protein content of late sown sunflower. Nasim et al (2012a) also reported optimum oil content when nitrogen was applied at 60 kg/ha and a decline as N increased to 240 kgN/ha. A significant (P 0.05) high protein content of 29.71%) was reported when N was applied at the rate of 150 kg/ha in Moldova (Yasin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%